A voz das ruas : resistência negra e feminina no Poetry Slam - Soares, Cibele Moni (2021)
The present work intends to approach Poetry Slam, a poetry movement that involves orality, performance, urban space and young protagonists, in the certainty that the democratization of society permeates the need to revise institutionalized values in the literary field. Utilizing their marginal voices, they insert themselves in the contemporary scene to break hegemonies and point to literature as a space to exist and resist. The slam poems Vozes da Revolução (2019) and Querem nos calar (2019) available on the Youtube platform will be analysed, aiming to explain how this movement can positively contribute to the reaffirmation of black and female identity, constituting itself as a mechanism of resistance against the oppression imposed by a racist and patriarchal society. The process of enslavement, which lasted in Brazil from 1550 to 1888, has left its mark to this day, while even after the abolition of slavery, there was an absence of projects that would reintegrate the newly liberated black population, relegating them to social exclusion, marginalization and degrading stigmas which persist and affect their descendants. Inserted in this community so susceptible to these difficulties, the black women are even more affected by all of these. In addition to the oppression suffered due to their racial belonging, they face prejudice and limitations arising from the gender issue. Being black is a condition that, within a patriarchal and racist context, hinders their social mobility as an individual, which explains why they remain part of this group located at the base of the social pyramid for so long. Against the system that oppresses them, black people and, specially, black women mobilize to claim their dignity that has been stolen by racism and sexism in favor of a more just and democratic society. Through the analysis of the performances and poetic productions of female black slammers, this research highlights the importance of alternative forms of awareness and nurture of recovering citizenship, promoted by the victims of these intersecting oppressions. Opposing the secular attempt at silencing them, these protagonists take their place of speech and bring new meaning to their existence through Poetry Slam, a way of making art, education and social policy.